Simulação computacional como ferramenta auxiliar ao ensino de Engenharia Elétrica em turbinas hidrocinéticas: desenvolvimento de ferramenta e de roteiro de experimentação - Santos, Rodrigo Silva dos (Brasil, 2021)
The main focus of the present study is to address the development of a computational simulation tool to assist undergraduate students in Electrical Engineering in teaching about hydrokinetic turbines. The general objective is to create such a tool using MATLAB software, with an experimentation script, to serve as a guide for undergraduate students to study the application of hydrokinetic turbines as a clean energy source, considering the characteristics of rivers in isolated communities in the Amazon region. To this end, the following specific objectives were defined conceptualize computational simulation as well as hydrokinetic turbines, enable the interaction between student and simulator, obtain numerical results and graphics in the output variables, interpret results, and create an experimentation script to guide the user in the necessary simulations, besides validating the simulator's applicability, comparing the 3 turbines under study in this work. Computer simulation for hydrokinetic turbines as a form of teaching in Electrical Engineering is justified because there are in the Amazon, population above 80,000 families that are not supplied by the National Main Grid being isolated communities that do not have full access to electricity, being hydrokinetic energy still little applied in Brazil, since these communities are located near rivers, which demonstrates their high potential in receiving this type of technology. The present study consists of a descriptive and quantitative research, based on the collection of information in primary sources related to the hydrokinetic turbines adopted for the study. With the information gathered throughout the research and the analysis of the information, it was possible to conclude that the computational simulation tool developed faithfully describes the behavior of each hydrokinetic turbine studied, making it possible to visualize the electric power generated according to the pre-established conditions of the river, as well as other results such as fluid conditions, electric power produced, torque and turbine rotation, fulfilling its role of motivating, at the academic level, future studies involving the development of the tool as well as the decision for hydrokinetic energy generation in isolated communities in the Amazon.